Predictors of subjective cognitive deficits in patients with mild cognitive impairment. Issue 2 (22nd December 2021) - Loessner, Lorenz; Matthes, Claudia; Haussmann, Robert; Brandt, Moritz D.; Sauer, Cathrin; Espin, Melanie; Noppes, Felix; Werner, Annett; Linn, Jennifer; Hummel, Thomas; Haehner, Antje; Donix, Markus
Abstract : Background: Detailed examination of cognitive deficits in patients with mild cognitive impairment (MCI) yields substantial diagnostic and prognostic value, specifically with respect to memory. Magnitude and characteristics of subjective cognitive deficits, however, often receive less attention in this population at risk for developing dementia. Methods: We investigated predictors of subjective cognitive deficits in patients with MCI, using a detailed assessment for such impairments associated with different cognitive domains, as well as demographic and clinical variables including magnetic resonance imaging data. Results: The strongest predictor for subjective memory deficits was depressed mood, whereas subjective performance issues associated with attention or executive functions also corresponded to measurable impairments in the respective cognitive domains. Reduced hippocampal thickness and hemispheric entorhinal cortex thickness asymmetry were associated with objective memory impairment but not with subjective deficits or symptoms of depression. Conclusions: Whereas low objective memory performance and reduced cortical thickness within medial temporal lobe subregions could be associated with neurodegeneration, greater subjective memory deficits in patients with MCI may indicate psychological burden.